STRUCTURE AND ELECTRONIC-PROPERTIES OF CESIUM-LOADED ZEOLITE-A - Armstrong, A; Anderson, P; Woodall, L; Edwards, P (1994)
The structure and electronic properties of the compound resulting from the reaction of cesium vapor with dehydrated cesium-exchanged zeolite A are reported here. Rietveld refinement of powder neutron diffraction data demonstrates the incorporation of at least two "excess" cesium atoms per primitive unit cell into the zeolite. The presence of the previously identified Cs4 linear unit was confirmed; in the present study, the different synthetic route leads to a higher concentration of the tetramer than previously reported, approaching one per primitive unit cell. Detailed structural analysis, using powder neutron diffraction, magnetic susceptibility, and electron spin resonance (ESR) studies, points to the formulation Cs42+ rather than the previously reported Cs43+. Accordingly, the compound is only weakly paramagnetic with less than 6% of the excess electrons forming localized paramagnetic centers. There are indications from the ESR g shift that this paramagnetism may originate from hole-based localized states, perhaps arising out of some partial charge fluctuation in an (otherwise) filled Cs42+ electronic band. Even for these paramagnetic centers, substantial electron-electron interactions lead to antiferromagnetic ordering below 10 K. Approximately three sodium ions per primitive unit cell resulting from incomplete ion exchange were identified; these also appear to carry some excess electron density, and there is evidence for segregation of sodium and cesium cations within the zeolite. © 1994 American Chemical Society.